Complete atrioventricular canal repair with a decellularized porcine small intestinal submucosa patch. (21st September 2018) - Al Haddad, Eliana; LaPar, Damien J.; Dayton, Jeffrey; Stephens, Elizabeth H.; Bacha, Emile
Abstract: Background: Congenital heart defects affect nearly 1% of all children born per year in the United States, and complete atrioventricular canal (CAVC) accounts for 2%‐9%. While several patch materials have been used for septal defect closure during CAVC repair, clear superiority of one material over another has yet to be established. Methods: A retrospective review of clinical outcomes following CAVC repair at Morgan Stanley Children's Hospital/Columbia University was performed on operations conducted from March 2010 to September 2017. Univariate and Kaplan‐Meir survival analyses were utilized to evaluate primary outcomes of interest following CAVC repair in the modern surgical era. Results: A total of 73 patients were analyzed, with an average operative age of 22 weeks. The majority (71%) of the patients underwent a 2‐patch repair. A CorMatrix patch was used for ventricular septal defect(VSD) closure in 77% of the patients, and/or in 75% of atrial septal defect closures. There was one in‐hospital mortality (1.4%) due to respiratory failure. One patient required a pacemaker. At mid‐term follow‐up (1.6 years), a total of 7 patients required 8 reoperations due to cardiac‐related indications, including 5 for left atrioventricular valve (LAVV) repair, 1 for LAVV replacement, and 2 isolated residual VSDs. Conclusion: A standardized repair for CAVC results in excellent outcomes in the current era, with low rates of reoperations. CorMatrix for the closure of CAVC has proven to produce good results with equivalent outcomes to other patch materials. Its ease of use and pliability make it an attractive alternative for consideration.